2021
DOI: 10.1039/d1ta03684j
|View full text |Cite
|
Sign up to set email alerts
|

Formation and operating mechanisms of single-crystalline perovskite NaNbO3 nanocubes/few-layered Nb2CTx MXene hybrids towards Li-ion capacitors

Abstract: Lithium-ion capacitors (LICs), combining both merits of lithium-ion batteries and supercapacitors, possess high energy/power density and long-duration lifespan in one device. However, the dynamic imbalance between the positive and negative...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 48 publications
1
33
0
Order By: Relevance
“…Benefiting from the synergistic effect of the superior electrical conductivity of MXene and robust crystal structure of single-crystal perovskite, the S–P–NNO NCs/f-Nb 2 CT x composites exhibited excellent rate capacity. AC//S–P–NNO NCs/f-Nb 2 CT x LICs could reach an ED of 56 Wh kg –1 at 13 kW kg –1 , along with 75% capacitance retention after 4000 cycles …”
Section: Applications In Micsmentioning
confidence: 99%
See 2 more Smart Citations
“…Benefiting from the synergistic effect of the superior electrical conductivity of MXene and robust crystal structure of single-crystal perovskite, the S–P–NNO NCs/f-Nb 2 CT x composites exhibited excellent rate capacity. AC//S–P–NNO NCs/f-Nb 2 CT x LICs could reach an ED of 56 Wh kg –1 at 13 kW kg –1 , along with 75% capacitance retention after 4000 cycles …”
Section: Applications In Micsmentioning
confidence: 99%
“…Distinctively, TB structure appears in the W–Nb–O system and can provide fast ion transport multichannels and show a small volume expansion . Additionally, the ABO 3 perovskite structure is composed of octahedrons and cations, and because of its strong lattice skeleton, can allow various combinations of anions and cations to exist in the structure, making this material an alternative for ion storage electrodes. , The special structures attributed to NBMOs are inextricably linked to their high rate performance and strongly support that the NBMOs as alternative anodes toward high-performance MICs.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Generally, by selective etching the A (element of group IIIA or IVA) layer of MAX phases, MXenes can be obtained with the formula of M n +1 X n T x , in which M represents the early transition metal, X indicates carbon or nitrogen or their mixture, T x denotes the surface functional groups introduced by etching, and n is 1–3 . MXenes show an exceeding electronic conductivity even higher than that of graphene and exhibit an excellent mechanical property and low ionic diffusion barrier for Li + (0.07 eV) along with surprising hydrophilicity properties resulting from their surface functional groups. , For these reasons, MXenes become promising candidate materials in LIBs and LICs as active materials and/or functionalized substrates. Unfortunately, the theoretical specific capacity of MXene (such as Ti 3 C 2 ) achieves only 320 mA h g –1 in LIBs, which is not enough to surpass other advanced anode materials . Moreover, like other 2D materials, MXene flakes have a great tendency to restacked, resulting in impeded Li + transmission and loss of active sites. Thus, inserting TMOs that provide high specific capacities into MXenes layers to prevent from their restacking is a good strategy and has aroused great interests.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the crack of the nanostructures, exfoliation from the conductive carbon, and nanoparticle aggregation are still inevitable, especially during long-term cycling . It has been demonstrated that the single-crystalline nanostructure can inhibit the structure crack during charge/discharge, achieving enhanced durability. , The single-crystal materials have the characteristics of more stable crystal structures that provide robustness of electrodes during cycling . Nevertheless, the preparation of these nanomaterials, especially single-crystalline nanomaterials, is usually very complicated and requires strict experimental conditions, making this nanomaterial production practical only on laboratory scales.…”
Section: Introductionmentioning
confidence: 99%